RELIGIOUS LIFE OF THE KUTA TRADITIONAL VILLAGE COMMUNITY IN THE INFLUENCE MODERNIZATION ERA - Miharja, Deni (UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract: So far, the influence of modernization has always been identified with urban communities because of the ease of accessing modernization products. However, the impact of modernization can also be felt by traditional and rural communities, and the influence of modernization thought by the people of Kampung Kuta Ciamis, West Java. This paper aims to reveal the understanding of the people of Kampung Kuta towards religion and modernization and how modernization influences the religious life of the people of Kampung Kuta. This study uses a qualitative descriptive method with a phenomenological approach. The research findings show that the people of Kampung Kuta have a firm understanding of Islam combined with traditional ceremonies going on for generations, such as the ceremony to build a new house, the presentation ceremony, the commemoration ceremony for Earth Day, and the babarit ceremony. The various traditions are essentially a form of gratitude, gain the benefit, and keep away harm. In understanding modernization, the people of Kampung Kuta Sudan can become players of modernization through the use of modernization products in the form of modern communication and transportation tools. They also welcomed the use of Kampung Kuta as one of the leading tourist destinations in Ciamis. The positive response of the indigenous people of Kampung Kuta to modernization shows that the theory of rejection of modernization by traditional communities is very relative, meaning that not all people with conventional (ancient) styles reject modernization. Keywords: Kampung Kuta, modernization, traditional tourism, traditional ceremonies Abstrak: Sejauh ini pengaruh modernisasi selalu didentikkan kepada masyarakat kota karena kemudahan dalam mengakses produk-produk modernisasinya. Namun, pengaruh modernisasi juga bisa dirasakan oleh masyarakat tradisional dan pedalaman, seperti halnya pengaruh modernisasi yang dirasakan oleh masyarakat Kampung Kuta Ciamis, Jawa Barat. Tulisan ini bertujuan mengungkap bagaimana pemahaman masyarakat Kampung Kuta terhadap agama dan modernisasi, serta bagaimana pengaruh modernisasi terhadap kehidupan keberagamaan masyarakat Kampung Kuta. Penelitian ini menggunakan metode kualitatif-deskriptif dengan pendekatan fenomenologis. Temuan penelitian menunjukkan bahwa masyarakat Kampung Kuta memiliki pemahaman agama Islam sangat kuat yang dipadukan dengan upacara-upacara adat yang sudah berlangsung turun temurun seperti upacara mendirikan rumah baru, upacara penyajian, upacara peringatan hari bumi, dan upacara babarit. Berbagai upacara yang dilaksanakan esensinya adalah bentuk rasa syukur, memperoleh kemaslahatan, dan menjauhkan marabahaya. Dalam pemahaman soal modernisasi, masyarakat Kampung Kuta sudah mampu menjaid pemain dari modernisasi melalui penggunaan produk-produk modernisasi berupa alat komunikasi dan transportasi modern. Mereka juga menyambut baik penggunaan Kampung Kuta sebagai salah satu destinasi wisata unggulan di Ciamis. Respon positif masyarakat adat Kampung Kuta terhadap modernisasi menunjukkan bahwa teori penolakan modernisasi oleh masyarakat tradisional sangat relative adanya, artinya tidak semua masyarakat dengan corak tradisonal (kuno) menolak modernisasi. Kata Kunci: Kampung Kuta, modernisasi, pariwisata adat, upacara adat.